The Impact of Employee Wellbeing Program, Work Motivation, And Work Discipline on Employee Productivity - Sano, Jesicca Putri; Firdausiah, Rr. Ayu (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of employee wellbeing programs, work motivation, and work discipline on employee productivity at the branch office of PT X. Design/Methodology/Approach – This study employs an explanatory quantitative research design. Data were collected through questionnaires distributed to all employees of the branch office of PT X using a saturated sampling technique. The data were analyzed using multiple linear regression with SPSS 27.0 for macOS to examine the relationships between employee wellbeing programs, work motivation, work discipline, and employee productivity. Findings – The results indicate that employee wellbeing programs have a positive and significant effect on employee productivity. Work motivation also has a positive and significant effect on productivity. Furthermore, work discipline positively and significantly influences employee productivity. These findings demonstrate that improving employee wellbeing, strengthening motivation, and maintaining work discipline are important strategies for enhancing productivity at the operational level. Originality/Value This research is original in integrating employee wellbeing programs, work motivation, and work discipline into a single empirical model. The findings provide practical value by offering evidence-based insights to improve productivity through comprehensive human resource management strategies.